Visible Borders, Invisible Economies: Living Death in Latinx Narratives - Ulibarri, Kristy L (Latinx: The Future Is Now, 2022)
Globalization in the United States can seem paradoxical: free trade coincides with fortification of the southern border, while immigration is reimagined as a national-security threat. US politics turn aggressively against Latinx migrants and subjects even as post-NAFTA markets become thoroughly reliant on migrant and racialized workers. But in fact, there is no incongruity here. Rather, anti-immigrant politics reflect a strategy whereby capital uses specialized forms of violence to create a reserve army of the living, laboring dead. Visible Borders, Invisible Economies turns to Latinx literature, photography, and films that render this unseen scheme shockingly vivid. Works such as Valeria Luiselli's Tell Me How It Ends and Alex Rivera's Sleep Dealer crystallize the experience of Latinx subjects and migrants subjugated to social death, their political existence erased by disenfranchisement and racist violence while their bodies still toil in behalf of corporate profits. In Kristy L. Ulibarri's telling, art clarifies what power obscures: the national-security state performs anti-immigrant and xenophobic politics that substitute cathartic nationalism for protections from the free market while ensuring maximal corporate profits through the manufacture of disposable migrant labor.